Enhancing the image and attractiveness of TVET - Ratnata, I Wayan [Verfasser] (My University, 2013)
"This paper gives some insight into the issues of the image and attractiveness of technical and vocational education and training (TVET) in Indonesia and in the efforts and measures to increase them. Data from China, India, South Korea and Russia show, that these countries have similar problems and apply similar strategies to overcome them. In most societies TVET graduates are not considered to be ready for work. This is due to many factors, among others: lack of facilities for practice, lack of linkages between schools and companies, a poor educational system, lack of teachers' qualifications, etc. Indonesia has made some breakthroughs in enhancing the image and attractiveness of TVET, among others, by increasing the share of vocational education and training with a target ratio between TVET and general high school education of 70% to 30% in 2025. Another step for enhancing the image and attractiveness of VET is establishing more higher education within vocational fields as has been done in China, or increasing the permeability from TVET to higher education as has been done in South Korea or India. The recent launch of the Indonesian Qualification Framework suggests equivalence of academic, vocational/professional education and competence development by work experience and further training, which could make TVET more attractive." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.3.4 Asien; I 2.2.2 Osteuropa; Berufsbildungssystem; Attraktivität; Indonesien; China; Südkorea; Russland